Impact of medical professionals on Carbapenem-resistant Pseudomonas aeruginosa: moderating effect of workload based on the panel data in China - Meng Han; Xinping Zhang (BMC, 2020)
Abstract Background Antimicrobial resistance (AMR), especially carbapenem-resistant Pseudomonas aeruginosa (CRPA), causes a serious increase in morbidity, mortality and costs. Medical professionals play an important role in curbing AMR. Previous studies overlooked the impact of workload on the relationship between medical professionals and AMR. This study aimed to explore the relationship between medical professionals and the CRPA rate as well as the moderating effect of medical professionals' workload on this relationship. Methods A provincial-level panel dataset from 2014 to 2017 was constructed. Medical professionals were measured by the numbers of physicians, registered nurses, pharmacists, and clinical microbiologists per 1000 population. Workload was measured by the number of daily physician visits. Fixed effect model and hierarchical regression analysis were performed to explore the moderating effect of workload on medical professionals and the CRPA rate. Results The numbers of physicians, registered nurses, pharmacists and clinical technicians were significantly negative associated with the CRPA rate (coef. = − 0.889, − 0.775, − 1.176, and − 0.822; P = 0.003, 0.003, 0.011, and 0.007, respectively). Workload had a significant and positive moderating effect on physicians, registered nurses, pharmacists, clinical technicians and the CRPA rate (coef. = 1.270, 1.400, 2.210, and 1.634; P = 0.004, 0.001, 0.035, and 0.003, respectively). Conclusions Increasing the number of medical professionals may help curb the CRPA rate. Measures aimed at reducing medical professionals' workload should be implemented to further improve CRPA performance.